Schindler: applying knowledge-based marketing in Japan - Holden, Nigel (Henry Stewart Talks, 2019)
This case study examines the Swiss manufacturer Schindler and its knowledge-based marketing activities in Japan and Asia. When expanding into Asia, Schindler successfully developed a knowledge based international marketing strategy that fused company explicit knowledge (on products, technology and competition) with local tacit knowledge, to ensure the business approach was naturally market-specific.